Hair-based flexible knittable supercapacitor with wide operating voltage and ultra-high rate capability. (April 2017) - Liu, Wenwen; Feng, Kun; Zhang, Yining; Yu, Tongwen; Han, Lei; Lui, Gregory; Li, Matthew; Chiu, Gordon; Fung, Pamela; Yu, Aiping
Abstract: Fiber-shaped supercapacitors (FSCs) are a promising candidate as power source or energy storage unit in wearable/stretchable electronics. However, it is still a significant challenge to design FSCs with excellent electrochemical performance while maintaining good flexibility to meet the requirement of wearable/stretchable electronics. Here, a flexible all-solid-state asymmetric FSCs has been rationally designed and successfully prepared with coaxial human hair/Ni/Graphene/MnO2 fiber as positive electrode and coaxial human hair/Ni/Graphene fiber as negative electrode. Importantly, the as-obtained FSCs show extraordinary flexibility and outstanding electrochemical performance with a wide potential window (1.8 V), excellent rate capability (up to 20, 000 mV s −1 ), fast frequency response ( τ 0 =55 ms), high volumetric energy density (1.81 mWh cm −3 ), long cycle stability. With the facile fabrication technology and low-cost raw materials, this strategy not only provides a reference for the construction of high-performance flexible FSCs, but also paves a new way to explore the next-generation portable/wearable energy storage devices. Graphical abstract: A novel type of human hair-based flexible knittable supercapacitor have proposed and designed, which exhibit ultra-high rate capability, high response frequency, wide operating voltage, and excellent cycle stability. Highlights: A flexible human hair/Ni/rGO/MnO2 fiber electrode is successfully constructed. The FSCs based on human hair/Ni/rGO/MnO2 fiber exhibit excellent performance. The FSCs follow the rules of series/parallel connections of ideal capacitor. These results make the FSCs a promising power source for flexible wear devices.